Metamorfismo das rochas máficas das regiões da serra do Tapa, Arapoema/Pau D’Arco, Juarina e Araguacema, Cinturão - CRUZ, Danilo José do Nascimento (2020)
Ophiolites that were found within the Araguaia Belt, a Neoproterozoic geotectonic unit, have been studied by the research group “Petrologia e Evolução Crustal”/CNPq-UFPA. As there was a lack of knowledge about the metamorphism of those newly found bodies, the present study focused on the mafic rocks that belong to the ophiolite sequences of the Serra do Tapa, Arapoema/Pau D’Arco, Juarina and Araguacema regions in order to identify the metamorphic transformations and conditions. At first, a literature review was made, followed by a collection of materials concerning the areas of study, such as thin sections and cartographic and geological base maps and databases. From petrographic and mineralogical analysis, it was possible to identify hypohyalline metabasalts with a paragenesis formed of Act + Ep + Ab + Chl in the Serra do Tapa region; hypohyalline metabasalts showing a paragenesis of Ab + Ep + Chl in the Arapoema/Pau D’Arco; hypocrystalline metabasalts with a paragenesis composed of Act + Ep + Ab+ Chl + Bt + Mt in the Juarina region; and hypohyalline basalts and metabasalts containing lithic fragments in the Araguacema region, with the latter showing the following paragenesis: Ep + Ab + Chl + Ser ± Qtz. Based on those mineral associations, it was possible to assure the occurrence of metamorphism in the studied areas. It was estimated metamorphic conditions in the lower greenschist-facies, with temperatures between 250 and 300ºC and pressures bellow 4 kb to the Serra do Tapa, Arapoema/Pau D’Arco and Araguacema regions; and higher greenschist-facies (biotite zone), with temperatures up to 400ºC and same pressures to the Juarina region. The microstructural analysis revealed the occurrence of microtextures caused by brittle deformation by cataclastic flow and ductile deformation by crystalline plasticity. It was also possible to infer, from the interpretation of all the data collected, that the metamorphic conditions and the degree of deformation increased from the west to the east, which is compatible with what has been reported in the scientific literature about the regional metamorphism of the Araguaia Belt.